Bi-perspective sulfur abatement options to mitigate coastal shipping ships emissions: A Case Study of Chinese coastal zone. (1st August 2021) - Zhong, Huiling; Guo, Chunhua; Yip, Tsz Leung; Gu, Yimiao
Abstract: In response to global sulfur emission restrictions, China has established sulfur emission control areas in its coastal areas. This has a huge impact on China's coastal shipping ships. These ships can adopt the following three sulfur abatement options to deal with it: (1) using low-sulfur fuel, (2) using an exhaust gas cleaning system, and (3) using alternative fuel Liquefied Natural Gas (LNG). This paper has established two models from two different perspectives to analyze the differences of abatement options between the shipowners and the general public. Sensitivity analyses are carried out on the factors affecting the sulfur abatement options, including remaining lifespan of ships, ship power, initial cost of sulfur abatement options, and fluctuations in the price of fuel. By analyzing the impact of these factors on the choice of the shipowners to reduce sulfur emission, this paper proposes some incentives and subsidy policies accordingly, which can provide references for policymakers. Graphical abstract: Image 1 Highlights: This paper optimizes sulfur abatement options in sulfur emission control areas novelly. It has established two models respectively in two different perspectives, namely the ship owners and the general public. A Chinese case is conducted to illustrate the models' applications. Incentive policies are proposed to inspire shipowners to choose options that are environmentally friendly and cost efficient. This paper can provide the references for policy makers. To our knowledge, till now, there is no literature doing this kind of research due to its latest happening.